HIV Genotype Analysis from HIV Infected Patients in East Java Area - Yulia Sari Ismail; Soetjipto Soetjipto; Eddy Bagus Wasito; Nasronudin Nasronudin (Universitas Syiah Kuala, 2012)
Human Immunodeficiency Virus type 1 (HIV-1) has been known to cause Acquired Immune Deficiency Syndrome (AIDS) disease and has been alaso divided into several subtypes (A, B, C, D, F, G, H, J, K) and Circulating Recombinant Form (CRF). Different characteristics of subtype of the virus and its interaction with host can affect the severity of the disease. This study was aimed to analyze HIV-1 genotypes circulating in HIV/AIDS patients from the East Java region descriptively. Information from this research was expected to complement the data of mocular epidemiology of HIV in Indonesia. This study used blood plasma from patients who had been tested to be HIV positive who were seeking treatment or are reffered to the Intermediate Care Unit of Infectious Disease (UPIPI) Dr. Soetomo Hospital Surabaya from various area representing the East Java regions. Plasma was separated from blood samples by centrifugation for use in the the molecular biology examination including RNA extraction, nested PCR using specific primer for HIV gp120 env gene region, DNA purifying, DNA sequencing, and homology and phylogenetic analysis. Based on the nucleotide sequence of the HIV gp120 env gene, it was found that the most dominant genotypes in East Java belonged to one group of Circulating Recombinant Form (CRF), namely CRF01_AE and CRF3x_01B, which has been also found in Southeast Asia. In the phylogenetic tree, most of HIV samples (30 samples) were in the same branch with CRF01_AE and CRF3x_01B, except one sample (HIV40) was in the same branch with subtype B.